Damage index changes in patients with systemic sclerosis: a retrospective analysis over a five-year period - A. V. Petrov; E. S. Krutikov; A. S. Gaffarova; A. A. Petrov; A. A. Gorlov (Научно-практическая ревматология)
Objective: to estimate the changes of the Scleroderma Clinical Trials Consortium Damage Index (SCTC-DI) over a five-year period in patients with systemic sclerosis (SS) according to the clinical type of the disease and the use of low doses of glucocorticoids (GCs), methotrexate (MTX), and hydroxychloroquine (HCQ).Subjects and methods. The data of a clinical observation in 68 patients with SSD were analyzed, by estimating the SCTC-DI at two time points: May-July 2019 and retrospectively in 2014. The changes of the index values were studied in the observed patients according to the SS type (diffuse, n=15 and limited, n=46) and treatment (low doses of GCs, n=29, MT, n=18 and HCQ, n=16) used for at least 36 months within 5 years.Results and discussion. The observed patients with SS over a five-year period showed increases in the average SCTC-DI from 3.91 to 6.73 and in the number of patients with SCTC-DI >1 from 76.4 to 88.2%. The increase in SCTC-DI in diffuse SS was more significant than in limited SS (its median was 5.10 [4.34; 6.35] and 2.19 [1.84; 3.06], respectively; p<0.05). Analysis of SCTC-DI dynamics established that in patients treated with MTX, the increase in the score for musculoskeletal system damage was less than in those untreated with this drug (its median was 0.24 [0.11; 0.33] and 0.63 [0.41; 0.75], respectively; p<0.05). The increase in the score for cardiovascular system damage during GC treatment was less significant than without this therapy (0.12 [0.05; 0.27] and 0.47 [0.31; 0.56], respectively; p<0.05). In patients receiving low-dose GCs, the increase in the score for gastrointestinal tract damage was more significant than without such therapy (1.02 [0.87; 1.21] and 0.73 [0.51; 0.83], respectively; p<0.05).Conclusion. The investigation demonstrated an increase in the values of all components of the SCTC-DI for damage to various organs and systems in SS over a five-year period. The SCTC-DI is a promising tool for evaluating the impact of ongoing therapy on the development of irreversible damage to the target organs of the SS disease process.